Association of characters in hand pollinated progenies of Hevea brasiliensis (Willd. ex. Adr. de Juss) Muell. Arg. - Licy J; Premakumari D (Indian Journal of Natural Rubber Research, 1988)
Nursery evaluation of sixty three genotypes of Hevea, obtained from 1982 hand pollinations was carried out for yield and related characters like plant height, girth, number of latex vessel rows and bark thickness. Simple, partial and multiple correlations of the variates were estimated. Yield on test tapping was positively correlated with all other characters. Plant height showed significant correlation with girth. Girth and number of latex vessel rows showed significant positive correlation with bark thickness. Studies on partial correlation revealed that number of latex vessel rows is the most important character influencing the nursery yield. The characters studied could explain 43 per cent of yield variability in the nursery stage.
Keywords: Hevea brasiliensis; Progeny analysis